EVALUATION OF MORPHOLOGICAL CHANGES OF THE PARANASAL SINUS IN COMPUTED TOMOGRAPHY AND MAGNETIC RESONANCE IMAGING MODALITIES - OJHA, SANTOSH; DEBNATH, MANNA; NIRAULA, ANUPAM; KHAN TAHIRI, SHAHNAWAZ ALI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The objective of the study was to evaluate the prevalence of pathological conditions and anatomical variations occurring within paranasal sinus among the patients undergoing computed tomography (CT) scan and magnetic resonance imaging (MRI) scan in Gurugram district. Methods: A prospective study was conducted among 20 patients in each modality, the patient undergoing the CT of paranasal sinus and patients undergoing routine MRI brain study. The clinical findings from CT and MRI were taken as primary data and later on compiled together under different variables to assess the occurrence of paranasal sinus disease and anatomical variations within. Results: The present study revealed that the most common pathology was mucosal thickening followed by polyp and the occurrence of air-fluid level; maxillary sinus being commonly affected. In patients undergoing CT, the most common anatomical variation was deviated nasal septum, that is, 16 out of 20 patients followed by the bone spur formation. In the patients undergoing routine MRI brain, most of the patient had mucosal thickening <5 mm. In the lining of maxillary sinus, moderate hyperintensity was reported. Conclusion: Based on the study, it is concluded that mucosal thickening is most commonly evident pathology with maximum occurrence seen in the maxillary sinus. The co-occurrence of more than 1 anatomical variation and involvement of multiple paranasal sinuses were seen positive. MRI was found more sensitive in assessing the early changes in sinus mucosal abnormalities.